Exposure To High-fat Style Diet Induced Renal And Liver Structural Changes, Lipid Accumulation And Inflammation In Intact And Ovariectomized Female Rats - Yamuna Sucedaram; Edward James Johns; Ruby Husain; Munavvar Abdul Sattar; Mohammed H Abdulla; Giribabu Nelli; Manizheh Khalilpourfarshbafi; Nor Azizan Abdullah; Nur Syahrina Rahim (Dove Press, 2024)
Indexed by WOS/Scopus/ERA